Avoiding Dark Corners : A Robust Monetary Policy Framework for the United States - Alichi, Ali (IMF Working Papers; Working Paper, 2015)
The Fed has taken several steps towards strengthening its monetary framework over the past several years. Those steps have supported the Fed's efforts to stimulate the economy through forward guidance despite being constrained by having policy rates at zero. We show that an optimal control approach to monetary policy, which includes the publication of a baseline forecast and a description of the uncertainties around that outlook, combined with an improvement in the Fed's communications toolkit, could further enhance the effectiveness of Fed policy. In the current conjuncture, such a risk management approach to monetary policy would result in both a later liftoff of policy rates and a modest, but planned, overshooting of inflation.